Development of suspended thermoreflectance technique and its application in thermal property measurement of semiconductor materials - Sarkar, Dipta (Kansas State University, 2020)
This dissertation details the development of a new scientific tool for the thermal characterization of freestanding micro/nano-scale materials, with specific application to thin films. The tool consists of a custom-designed and calibrated opto-electric system with superior spatial and temporal resolutions in thermal measurement. The tool, termed as Suspended ThermoReflectance (STR), can successfully perform thermal mappings at the submicron level and is able to produce unconstrained thermal conductivity unlike other optical measurement techniques where independent conductivity measurement is not possible due to their reliance on heat capacity. STR works by changing the temperature of a material and collecting the associated change in light reflection from multiple points on the sample surface. The reflection is a function of the material being tested, the wavelength of the probe light and the composition of the specimen for transparent and quasi-transparent materials. Coupling the change in reflection, along the sample’s length, with the knowledge of heat conduction allows for the determination of the thermal properties of interest. A thermal analytical model is developed and incorporated with optical equations to characterize the conductivity of thin films. The analytical model is compared with a finite element model to check its applicability in the STR experiment and data analysis. Ultimately, thermal conductivity of 2 µm and 3 µm thick Si samples were determined using STR at a temperature range of 20K – 350K and compared to literature as a validation of the technique. The system was automated using a novel LabView-based program. This program allowed the user to control the equipment including electronics, optics and optical cryostat. Moreover, data acquisition and real-time monitoring of the system are also accomplished through this computer application. A description of the development, fabrication and characterization of the freestanding thin films is detailed in this dissertation. For the most part, the thin films were fabricated using standard microfabrication techniques. However, different dry and wet etching techniques were compared for minimum surface roughness to reduce light scattering. The best etching technique was used to trim the Si films for the desired thicknesses. Besides, vapor HF was used to avoid stiction-failure during the release of suspended films.
Keywords: Thermoreflectance; Thermal conductivity; Silicon; Thin film; One dimensional heat transfer